Interdisciplinary Collaboration in Future Healthcare: Building Holistic Patient-Centered Models - Agnomelsya Bangaran; Adam Idris; Siti Mariam (Yayasan Adra Karima Hubbi, 2025)
Healthcare systems are increasingly challenged by complex patient needs, chronic conditions, and fragmented service delivery. Interdisciplinary collaboration has been widely promoted as a strategy to support holistic and patient-centered care, yet its practical implementation in future healthcare systems remains uneven and context-dependent. This study aims to examine how interdisciplinary collaboration contributes to the development of holistic patient-centered models in future healthcare and to identify key factors influencing its effectiveness across different healthcare contexts. A qualitative descriptive approach was employed using a systematic review of secondary data and comparative case analysis. Data were collected from peer-reviewed literature, policy reports, and documented interdisciplinary care models across various regions. The data were analyzed through thematic synthesis and cross-case comparison. The findings indicate that interdisciplinary collaboration enhances care coordination, patient engagement, and holistic service delivery when supported by organizational commitment, shared leadership, and effective communication. Collaboration outcomes vary according to healthcare system maturity, policy alignment, and professional culture. Patient involvement emerges as a critical element in successful interdisciplinary models.